Haematology and serum biochemistry of pigs fed grower feed fortified with cocoa (Theobroma cacao) seed testa - Olabisi Akinduro V.; Kehinde Asaniyan E.; Osunkeye Jacob O.; Olusola Fakolade P.; Mojijolajesu Adeosun J. (Journal of Agricultural Sciences (Belgrade), 2022)
The on-farm attempt to cut down feed costs through bulk fortification of standard animal feed with available cheap conventional feed ingredients or wastes had been a normal practice without a known empirical impact on livestock health and wellbeing. Therefore, this study determined the haematological parameters and serum biochemistry of pigs fed cocoa (Theobroma cacao) seed testa at varying inclusion levels in the formulated standard grower pig feed; T1:0% CST, T2:25% CST, T3:50% CST, T4:75% CST and T5:100% CST. Thirty (30) 8-week-old pigs were randomly assigned to the five treatments of six pigs each and replicated thrice, with two pigs per replicate in a completely randomised design (CRD). The experiment lasted for 10 weeks. At the end of the feeding trial, blood samples were collected randomly from three pigs per treatment through the jugular vein using hypodermic needle and syringe for haematological analysis and serum biochemistry. This study recorded significant differences (P<0.05) in most of the haematological parameters, except for white blood cell (WBC), platelet and heterophils; apart from high-density lipoprotein, all serum biochemical indices were also significantly different (P<0.05). Haematological parameters and serum indices were within the normal range for the healthy pig, except for lymphocytes. However, based on the results of the haematological indices and the serum biochemical parameters, it could be concluded that cocoa seed testa at the 25% inclusion level in the standard grower pig feed had the optimum support for the wellbeing and healthy performance of pigs.